KOMPETENSI PEDAGOGIK GURU (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractPedagogical competence is one of important competencies to the teachers. Therefore, this study aims to determine how the pedagogical competence of teachers is, viewed from the aspects of learning knowÂledge skills, preparation of lesson plans, and learning in the classroom. This study used the quantitative method with 631 respondents of civil servant teachers of Islamic Education at school and teachers of geÂneral subjects at madrasah (Islamic school) recruited from non-permanent teachers in 20 districts/cities in Central Java province, selected at random. The findings show that teachersâ€™ pedagogical competence knowledge on the aspect of learning knowledge skills is in the â€œpoorâ€ category, the aspect of studentsâ€™ potential development knowledge and reflective efforts to improve the learning quality becomes a very weak point at an average value with the â€œvery poorâ€ category. In addition, the aspect of ability to prepare lesson plans is in the â€œsufficientâ€ category, the teaching material organization and the evaluation aspect are very weak competence aspects, which get â€œpoorâ€. Meanwhile, the competence of learning implemenÂtation aspect is in the â€œsufficientâ€ category. AbstrakKompetensi pedagogik merupakan salah satu kompetensi yang penting bagi guru. Untuk itu, penelitian ini bertujuan untuk mengetahui bagaimana kompetensi pedagogik guru, dilihat dari aspek kemampuan pengetahuan pembelajaran, menyusun rancangan pembelajaran (RPP), dan pembelajaran di kelas. Penelitian ini menggunakan metode kuantitatif dengan responden 631 guru PNS Pendidikan Agama Islam pada sekolah dan guru mata pelajaran umum pada madrasah yang direkrut dari guru honorer di 20 Kabupaten/Kota di Provinsi Jawa Tengah yang dipilih secara random. Hasil penelitian menunjukkan bahwa kompetensi pedagogik guru pada aspek kemampuan pengetahuan pembelajaran dalam kategori â€œkurangâ€, aspek pengetahuan pengembangan potensi peserta didik dan upaya reflektif untuk meningkatkan mutu pembelajaran menjadi titik yang sangat lemah dengan mendapat nilai rata-rata dengan kategori â€œsangat kurangâ€. Selain itu, aspek kemampuan menyusun RPP dalam kategori â€œcukupâ€, aspek pengorganisasian materi ajar dan aspek evaluasi merupakan aspek kemampuan yang sangat lemah dengan mendapatkan nilai â€œkurangâ€. Sedangkan, aspek kemampuan dalam melaksanakan pembelajaran dalam kategori â€œcukupâ€.
Keywords: Competence; Pedagogy; Teachers; Kompetensi; Pedagogik; Guru.